Molecular mechanisms of phosphorylation-regulated TTP (tristetraprolin) action and screening for further TTP-interacting proteins. (24th November 2010) - Tiedje, Christopher; Kotlyarov, Alexey; Gaestel, Matthias
Abstract : TTP (tristetraprolin) is an RNA-binding protein which regulates mRNA stability or translation or both. The molecular mechanisms which are responsible and which discriminate between regulation of mRNA stability and translation are not completely understood so far, but are clearly dependent on p38 MAPK (mitogen-activated protein kinase)/MK (MAPK-activated protein kinase) 2/3-mediated phosphorylation of TTP. To learn more about these mechanisms, phosphorylation-dependent TTP-interacting proteins could be of great interest. Many interacting partners, which belong to the mRNA-processing and -regulating machinery, have been identified by hypothesis-driven co-immunoprecipitation and in the classical Y2H (yeast two-hybrid) approach, where TTP was identified as prey, and are summarized in the present paper. However, because of transactivating properties of TTP, an unbiased Y2H approach using TTP as bait was hindered. Since novel methods for the identification of phosphorylation-dependent interaction partners and of interactors of full-length auto-activating proteins in eukaryotic systems have evolved in the last few years, these methods should be applied to screen for additional phosphorylation-dependent interaction partners of TTP and could lead towards a complete understanding of TTP function at the molecular level.